Characterizing acclimation of pansy and petunia to CO₂ enrichment for controlled environment production - McKinney, David Wayne, author; Craver, Joshua, advisor; Pilon-Smits, Elizabeth, committee member; Bauerle, Bill, committee member (Colorado State University. Libraries, 2021)
While crops often respond immediately to enriched CO2 concentrations (e.g., increased photosynthesis), this initial response is often not sustained throughout production, reducing the benefit of this input. For horticulture species, the timing and extent of these acclimation responses is still widely uncertain. Therefore, the objective of this research was to determine species-specific acclimation responses to enriched CO2 concentrations for pansy (Viola ×wittrockiana 'Matrix Blue Blotched Improved') and petunia (Petunia ×hybrida 'Dreams Midnight) during both propagation and finishing. To investigate the effects of enriched CO2 concentrations on pansy and petunia during finishing production, seedlings were transplanted into 11.5-cm pots and placed in growth chambers with air temperature, relative humidity, and radiation intensity setpoints of 21 °C, 55%, and 250 µmol∙m–2∙s–1, respectively. Carbon dioxide treatments were established using the two growth chambers with setpoints of either 400 (ambient) or 1000 μmol·mol–1 (enriched) maintained during a 16-h photoperiod. In addition to data collected through destructive harvest, rate of photosynthesis (A) in response to increasing internal leaf CO2 concentration (A-Ci) and ambient CO2 concentration (A-Ca) were measured weekly with a portable leaf photosynthesis system at saturating (A-Ci; 1000 µmol∙m–2∙s–1) or production (A-Ca; 250 µmol∙m–2∙s–1) radiation intensities. For both pansy and petunia, plants grown under the enriched CO2 concentration produced higher total shoot dry mass compared to ambient after 4 weeks. However, decreased maximum rate of photosynthetic electron transport (Jmax), maximum rate of Rubisco carboxylase (Vcmax), and similar photosynthesis at operating Ci concentration were observed under the enriched CO2 concentration after 4 weeks. Additionally, A measured at 1000 and 400 μmol·mol–1 was lower for both pansy and petunia grown under the enriched compared to ambient CO2 concentration based on A-Ca responses after 1 week, further indicating quick physiological acclimation to this input. This indicates little benefit of elevated CO2 to increase plant quality during the finishing stage of production in pansy and petunia, however there is possible marginal benefit due to increased biomass with no effect on overall plant size. To evaluate the impact of CO2 enrichment at varying timing and duration during propagation, pansy and petunia seeds were sown in 128-cell trays and placed in growth chambers with air temperature, relative humidity, and radiation intensity setpoints of 21 °C, 55%, and 250 µmol∙m–2∙s–1, respectively. Carbon dioxide treatments were established using the two growth chambers with setpoints of either 400 (ambient) or 1000 μmol·mol–1 (enriched) maintained during a 16-h photoperiod. Treatments consisted of seedlings grown for 28 days at ambient (Amb28), 28 days at elevated (Elv28), 14 days at ambient then 14 days at elevated (Amb14:Elv14), and 14 days at elevated then 14 days at ambient CO2 concentration (Elv14:Amb14). Harvest data was collected weekly, and four weeks after germination seedlings were transplanted into the greenhouse to determine impacts on finishing quality and flowering. Pansy and petunia produced higher total dry mass (roots + leaves + stem) under Elv28 and Amb14:Elv14 compared to Amb28 after 4 weeks, but showed no difference in leaf area. Additionally, plants grown under Elv28 and Amb14:Elv14 produced higher leaf mass area than Amb28 and Elv14:Amb14 for both species. Pansy showed decreased days to flower under Elv28, but no difference in biomass or size after transplant into the greenhouse. Therefore, elevated CO2 during seedling production may influence days to flower but does not contribute to growth rate long term after transplant. Likewise, similar morphological responses can be achieved with elevated CO2 being applied during the last two weeks of seedling production compared to elevation throughout the propagation stage. These results provide useful information regarding the timing and extent of physiological acclimation in response to enriched CO2 concentrations for pansy and petunia. However, due to physiological acclimation potentially occurring within one week of treatment initiation, additional research is needed to best understand how this input can be further optimized for controlled environment production.
Keywords: carbon dioxide; floriculture; physiology; controlled environments; acclimation; photosynthesis